2009
DOI: 10.1016/s0140-6736(09)60609-7
|View full text |Cite
|
Sign up to set email alerts
|

Pancreas transplantation

Abstract: Since the introduction of pancreas transplantation more than 40 years ago, efforts to develop more minimally invasive techniques for endocrine replacement therapy have been in progress, yet this surgical procedure still remains the treatment of choice for diabetic patients with end-stage renal failure. Many improvements have been made in the surgical techniques and immunosuppressive regimens, both of which have contributed to an increasing number of indications for pancreas transplantation. This operation can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
268
2
19

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 309 publications
(292 citation statements)
references
References 117 publications
3
268
2
19
Order By: Relevance
“…However, thereafter it reverses with transplanted patients performing better at 1 year. 5 The EUROSPK study 6 reported a much higher 44.8% rejection rate than that in our study (11.8%), but we continued steroids for Ն6 months after transplantation, which may in part explain the difference. Four of our patients lost their grafts due to rejection: 1 pancreas and kidney loss, 2 kidney losses, and 1 sole pancreas loss.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…However, thereafter it reverses with transplanted patients performing better at 1 year. 5 The EUROSPK study 6 reported a much higher 44.8% rejection rate than that in our study (11.8%), but we continued steroids for Ն6 months after transplantation, which may in part explain the difference. Four of our patients lost their grafts due to rejection: 1 pancreas and kidney loss, 2 kidney losses, and 1 sole pancreas loss.…”
Section: Discussioncontrasting
confidence: 56%
“…1 Two important recently published papers have concluded that SPKT provides a significant extension to patient life, 1 namely 10 years longer than that of KTA from a deceased donors. 5 Our perception is that SPKT patients are really difficult to manage not only in the early period, but also in follow-up. Complications are frequent; costs are high and directly related to the complication rate.…”
Section: Discussionmentioning
confidence: 99%
“…Simultaneous pancreas–kidney (SPK) transplantation restores insulin secretion and renal function in T1D patients with end‐stage renal disease (ESRD) 8. However, recipients may develop posttransplant diabetes, a broad clinical entity with multifactorial etiology including effects of immunosuppression, insulin resistance, weight gain, and others 9, 10.…”
Section: Introductionmentioning
confidence: 99%
“…However, recipients may develop posttransplant diabetes, a broad clinical entity with multifactorial etiology including effects of immunosuppression, insulin resistance, weight gain, and others 9, 10. With advances in immunosuppression, acute rejection has become less prevalent and immunological failures are typically ascribed to chronic rejection 8. However, another potential cause of immunological failure is T1D recurrence 11, 12.…”
Section: Introductionmentioning
confidence: 99%
“…En concordancia con resultados obtenidos en grandes centros [12][13][14] , en esta experiencia la sobrevida de pacientes fue de 70%, la sobrevida de páncreas 72% y la sobrevida de riñón fue de 73% en 10 años cifras superiores a la sobrevida de diabéticos en diálisis en lista de espera de trasplante, que es 46% a cuatro años 15 . Al fi nal del período de observación 9 pacientes estaban euglicémicos en ayunas, presentaban niveles normales de Péptido C e independencia de insulina o hipoglicemiantes orales, independencia de diálisis en 8 pacientes.…”
Section: Discussionunclassified